Methemoglobinemia after local anesthesia with prilocaine in adults: four case reports - Yılmaz, Meltem; İşcan, Arif and Mutlu, Levent (The European Research Journal, 2024)
Methemoglobinemia is a serious hematological disease characterized by the incapability of sufficient oxygen delivery to tissues and cyanosis when iron within hemoglobin in ferrous form (Fe+2) is oxidized to ferric form (Fe+3). Methemoglobinemia may be congenital or acquired. While prilocaine-induced methemoglobinemia can be seen in newborns and early pediatric ages, it is a rare condition in adults. We aimed to investigate prilocaine-induced adult methemoglobinemia with four cases.